2013
DOI: 10.1371/journal.pone.0061592
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of p.V37I Variant of GJB2 in Mild or Moderate Hearing Loss in a Pediatric Population and the Interpretation of Its Pathogenicity

Abstract: A p.V37I variant of GJB2 has been reported from subjects with moderate or slight hearing loss especially in East Asian populations. This study aimed to estimate the prevalence of the p.V37I variant among such subjects and prove, epidemiologically, its pathogenic potential to cause mild hearing loss. A total of 380 subjects from 201 families with hearing loss were enrolled. From them, 103 families were selected who had autosomal recessive inheritance or sporadic occurrence of hearing loss and who were younger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood as described previously, 8 and that from our 11 probands was subjected to whole-exome sequencing (WES). A SureSelect 50 Mb Hybridization and Capture kit was used for WES, and sequencing was performed using a HiSeq2000.…”
Section: Dna Preparation and Whole-exome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from peripheral blood as described previously, 8 and that from our 11 probands was subjected to whole-exome sequencing (WES). A SureSelect 50 Mb Hybridization and Capture kit was used for WES, and sequencing was performed using a HiSeq2000.…”
Section: Dna Preparation and Whole-exome Sequencingmentioning
confidence: 99%
“…However, a subset of deafness caused by GJB2 mutations (DFNB1), particularly in individuals carrying the p.V37I allele, is associated with mild to moderate hearing loss. [6][7][8] Recessive mutations in the OTOG, OTOGL, and STRC genes also are implicated in moderate hearing loss, rather than severe to profound hearing loss, in children. [9][10][11] Alterations in autosomal dominant (AD) deafness genes can manifest expectantly as hearing loss starting in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…However, over time, the mutation has been identified in numerous homozygous or compound heterozygous individuals with moderate hearing loss (median 25-40 dB; Kim et al, 2013). It has been concluded that p.V37I is a hypomorphic allele which may cause a less severe phenotype than c.235delC, and the p.V37I/c.235delC mutations do lead to mild to moderate hearing loss (Snoeckx et al, 2005;Schrijver & Chang, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Three mutations,c.35delG,c.167delT,and c.235delC, are found to be the most frequent mutations in Caucasian, Ashkenazi Jews, and East Asian populations, respectively (Morell et al, 1998;Roux et al, 2004;Tsukada et al, 2010). The polymorphisms are diverse and complex as well; p.V27I and p.E114G are commonly described as polymorphic variants in East Asian countries (Han et al, 2008) while the p.V37I variant, originally described as an innocent polymorphism, was recently suggested to contribute to the pathogenesis of moderate hearing loss in a Korean population (Pollak et al, 2007;Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the subjects' young age, the ABR threshold and/or ASSR were recorded, and mean thresholds at frequencies in the 0.5-4 kHz range were averaged to obtain an approximation for directional conditioned reflex. For children lacking behavioral thresholds and ASSR results, the ABR threshold is considered the high-frequency auditory threshold (12,13). We excluded patients with discriminated hearing loss curves.…”
Section: Genetic Testing Results and The Nature Of Hearing Lossmentioning
confidence: 99%